ANALISIS PENGARUH DIVERSIFIKASI PENDAPATAN, DIVERSIFIKASI ASET, INTEREST INCOME, DAN TRADING INCOME TERHADAP RETURN ON ASSETS DI PERBANKAN YANG GO PUBLIC DI BEI TAHUN 2015-2021 - Neisya Hafizha Swaskarina; Irene Rini Demi Pangestuti (Jurnal Akuntansi dan Pajak, 2023)
Recent economic development trends coupled with intense competition and deregulation in the Indonesian banking industry have encouraged banks to diversify and offer income to customers. Banking itself has a way of measuring ability that aims to generate profits, and one of the profitability ratios that can be used as a benchmark is the return on assets. So that this research was conducted to analyze the effect of income diversification, asset diversification, interest income, and trading income on the return on assets in banks in Indonesia that have gone public on the IDX within a period of seven years, namely 2015-2021. The research uses secondary data obtained from the Bloomberg Equity Screening (EQS) of commercial banks operating in Indonesia and registered on the IDX using a period of up to seven years, namely 2015 to 2021 due to obtaining an adequate sample size. From the observations that have been made, a sample of 41 banks is obtained among the 48 population because there are 7 banks whose financial statements are incomplete. After testing with the classic assumption test and regression, three independent variables were obtained, namely income diversification, asset diversification, and interest income which had a positive and significant effect on return on assets, while the trading income variable had a positive but not significant effect on return on assets. Keywords: income diversification, asset diversification, interest income, trading income, return on assets, commercial banks, stock exchange.